Expression pattern and network visualization of genes involved in milk persistency in bovine mammary tissue - Saedi, Naghmeh; Aminafshar, Mehdi; Chamani, Mohammad; Honarvar, Mahmood; Javadmanesh, Ali (Agriculture and Natural Resources, 2022)
Importance of the work: While several studies investigated the transcriptome of bovine mammary tissue; the cellular, biological processes and metabolic pathways of differentially expressed genes involved in lactation period in bovine have not been completely considered. Objectives: The objective was to identify the differentially expressed genes (DEGs) during the lactation period and the important genes involved in the effective metabolic pathways and biological processes involved in this period. Materials & Methods: The expression profile developed from the Gene Expression Omnibus database of the NCBI consisted of mammary tissue samples of lactating cows from +1 d (n = 8), +15 d (n = 8), +30 d (n = 8), +60 d (n = 6), +120 d (n = 6), +240 d (n = 5) and 300 d (n = 5). DEGs were determined using the limma package. The protein-protein interaction (PPI) network of DEGs was drawn using Cytoscape and significant gene clusters were identified using the MCODE application. The metabolic pathways and biological processes of the DEGs were analyzed using ClueGo. Results: In total, 344 DEGs were identified during lactation and eight significant clusters were recognized. CTNNB1, TNF, CDH1 and SPP1 had the highest degrees of connectivity in the PPI network. DEGs were enriched in metabolic pathways such as the adherens junction and TGF-beta signaling pathway. Main finding: Overall, due to the important role of CTNNB1, TNF and CDH1 in the adherens junction and TGF-beta signaling pathway, overexpression of these genes may affect these pathways that are involved in lactation. Some significant DEGs, such as SPP1, could affect lactation persistency However, more experiments are needed to confirm these results.